HIV-1 intron-containing RNA expression induces innate immune activation and T cell dysfunction - Akiyama, Hisashi; Miller, Caitlin M.; Ettinger, Chelsea R.; Belkina, Anna C.; Snyder-Cappione, Jennifer E.; Gummuluru, Suryaram (Nature communications, 2018)
Low levels of type I interferon (IFN-I) are thought to be a driving force for immune activation and T-cell exhaustion in HIV-1 infected individuals on combination antiretroviral therapy (cART), though the causative mechanisms for persistent IFN-I signaling have remained unclear. Here, we show Rev–CRM1-dependent nuclear export and peripheral membrane association of intron-containing HIV-1 RNA, independent of primary viral sequence or viral protein expression, is subject to sensing and signaling via MAVS, resulting in IFN-I-dependent pro-inflammatory responses in macrophages. Additionally, HIV-1 intron-containing-RNA-induced innate immune activation of macrophages leads to upregulation of inhibitory receptor expression and functional immune exhaustion of co-cultured T cells. Our findings suggest that persistent expression of HIV-1 intron-containing RNA in macrophages contributes to chronic immune activation and T-cell dysfunction and that use of HIV RNA expression inhibitors as adjunct therapy might abrogate aberrant inflammation and restore immune function in HIV-infected individuals on cART. Type I Interferon is thought to be a driving force for immune activation and T cell exhaustion during HIV infection. Here the authors show that intron-containing HIV RNA induces innate immune activation resulting in associated T cell dysfunction.